Family Support and Elderly Participation in Posbindu Activities: A Cross-Sectional Study at Urug Public Health Center, Tasikmalaya - Ardiansah Abdillah, Rifan; Falah, Miftahul; Saryomo; Muksin, Asep (Gaster, 2025)
Background: Indonesia is entering an aging population phase, in line with the global increase in the number of older adults. The World Health Organization (WHO) reports that more than 700 million people are aged 65 years and over worldwide, a figure projected to rise sharply by 2050. In response, the Indonesian government established the Integrated Development Post (Posbindu) to promote early detection, monitoring, and prevention of non-communicable diseases among the elderly. Objective: This study aimed to examine the relationship between family support and elderly participation in Posbindu activities at Urug Public Health Center, Tasikmalaya. Methods: A quantitative descriptive correlational design with a cross-sectional approach was applied. The study population included 189 elderly individuals aged 60 years. A purposive sampling technique was used to recruit 51 respondents. Data were collected using a family support questionnaire and Posbindu attendance records. Bivariate analysis was conducted using the Spearman rank correlation test. Results: The findings showed that 35 respondents (68.6%) reported receiving family support, while 16 (31.4%) did not. Statistical analysis revealed a significant correlation between family support and elderly participation in Posbindu activities (p = 0.000, p < 0.05). Conclusion: Family support is crucial in encouraging elderly participation in Posbindu programs. Strengthening family involvement and health worker initiatives may enhance community-based elderly care and ensure the sustainability of Posbindu activities.